2D lanthanide MOFs driven by a rigid 3, 5-bis(3-carboxy-phenyl)pyridine building block: solvothermal syntheses, structural features, and photoluminescence and sensing properties. Issue 34 (22nd July 2016) - Yang, Li-Zi; Wang, Jun; Kirillov, Alexander M.; Dou, Wei; Xu, Cong; Fang, Ran; Xu, Cai-Ling; Liu, Wei-Sheng
Abstract : New lanthanide MOFs display notable sensing ability for Cu 2+ ions and 2, 4, 6-trinitrophenol. Abstract : A new series of five lanthanide(iii ) metal–organic frameworks with a general formula of [Ln3 (bcpb)4 (μ-HCOO)(μ-H2 O)(H2 O)2 (DEF)] n (1–5 ) was generated by solvothermal reactions from Ln(NO3 )3 ·6H2 O {Ln = Eu (1 ), Tb (2 ), Gd (3 ), Dy (4 ), and Sm (5 )} and 3, 5-bis(3-carboxyphenyl)pyridine (H2 bcpb) in an aqueous N, N -diethylformamide (DEF) medium. The obtained products were characterized by elemental analysis, FT-IR spectroscopy, thermogravimetric analysis (TGA), and powder and single crystal X-ray diffraction. The latter reveals that all compounds (1–5 ) are isostructural and feature very intricate 2D metal–organic frameworks. These were topologically analyzed, revealing a very complex hexanodal underlying net that can be simplified further to a binodal 3, 5-connected layer with the 3, 5L52 topology. Solid-state photoluminescence properties of1–5 were studied in detail. Compound1 exhibits a strong red luminescence upon excitation at 338 nm and its lifetime is 532 μs. Compound2 shows an intense green luminescence upon excitation at 336 and its lifetime is 981 μs. The triplet state ( 3 ππ*) of bcpb 2− studied by using the Gd(iii ) derivative3 demonstrated that the ligand effectively populates Tb(iii ) emission ( Φ = 70.96%), whereas the corresponding Eu(iii ) derivative1 shows a weak luminescence efficiency ( Φ = 15.81%) as the triplet state of bcpb 2− has a poor match with the 5 D0 energy level of Eu(iii ). A notable feature of1 is its remarkable sensing ability for Cu 2+ ions and 2, 4, 6-trinitrophenol (TNP). Besides, a series of heterobimetallic Tb-based MOFs, [Tb3(1− x ) Eu3 x (bcpb)4 (μ-HCOO)(μ-H2 O)(H2 O)2 (DEF)] n { x = 0.001, 0.002, 0.003, 0.01, 0.02, 0.03, 0.04, 0.10, 0.15, 0.20} (compounds2a–2j, respectively), was prepared. The luminescence studies reveal that the simultaneous presence of the characteristic sharp emission bands of Eu 3+ and Tb 3+ allows the tuning of the photoluminescence colors of such materials by adjusting the doping concentration of the Eu 3+ ions.